2020
DOI: 10.9734/jeai/2020/v42i130452
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Path Coefficient Analysis for Yield and Yield Components in Late Maturing Pro-vitamin A Synthetic Maize (Zea mays L.) Breeding Lines

Abstract: This study was conducted in a rainforest ecology of Southwestern Nigeria during 2016 and 2017 cropping seasons under rainfed conditions to estimate character association and path coefficient of grain yield (t ha-1) and its component characters, to identify characters whose selection could be used in improving maize grain yield (t ha-1). Fourteen late-maturing pro-vitamin A maize (PVAM) synthetics were conducted in a randomized complete block design with three replications. The following agronomic characters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…From this study, grain yield showed positive and significant correlation with number of plants per plot, number of plants harvested, number of ears harvested and field weight at both phenotypic and genotypic levels, indicating that selection for these characters may be important in improving grain yield. This is similar to the findings of Olawamide and Fayeun [14]. Significant positive correlation was observed between days to 50% anthesis and days to 50% silking, as well as between ear height with plant height [15,16,17].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…From this study, grain yield showed positive and significant correlation with number of plants per plot, number of plants harvested, number of ears harvested and field weight at both phenotypic and genotypic levels, indicating that selection for these characters may be important in improving grain yield. This is similar to the findings of Olawamide and Fayeun [14]. Significant positive correlation was observed between days to 50% anthesis and days to 50% silking, as well as between ear height with plant height [15,16,17].…”
Section: Discussionsupporting
confidence: 87%
“…Significant positive correlation was observed between days to 50% anthesis and days to 50% silking, as well as between ear height with plant height [15,16,17]. Similarly, plant height correlated significantly and positively with days to 50% silking and days to 50% anthesis [16], number of ears harvested with number of plants per plot, field weight with number of plants per plot, and number of plants harvested with number of ears harvested [14]. This suggests that improvement of one character will automatically lead to improvement of the other simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of these three characters will most likely result in an increase in the yield capability of the maize population [1] and these characters can be considered for indirect selection to increase grain yield. [15]. The significant positive correlation between the two characters indicates that the characters can be improved simultaneously in the selection program due to the strong relationship between the two characters [15].…”
Section: Correlation Coefficientmentioning
confidence: 99%
“…The significant positive correlation between the characters implies that these characters can be simultaneously improved by selection in a breeding program due to the strong association between them (Olawamide et al, 2020). Hence, the characters: cob weight, ear diameter, ear length, no.…”
Section: Phenotypic Correlation Coefficientmentioning
confidence: 99%